The Canadian Association of Gastroenteroloy - Are You a Member Yet? - Pierre Paré; David Pearson; Nathalie Vergnolle (Canadian Journal of Gastroenterology)
Since its inception in 1962, the Canadian Association of Gastroenterology (CAG) has grown from a handful of physicians into an impressive and diverse membership of almost 1000 (Figure 1). Remaining true to the philosophy of its founders, the Association is a multidisciplinary organization comprised of gastroenterologists, hepatologists, pediatricians, surgeons, radiologists, internists, clinical and basic scientists, nurses, research coordinators, residents, medical students and representatives of industry. Members share the common goals of supporting and engaging in the study of the digestive tract in health and disease, and promoting the advancement of gastroenterology by providing leadership in patient care, research, teaching and continuing professional development.